Synchrotron and inverse-Compton emission from blazar jets - II. An accelerating jet model with a geometry set by observations of M87 - Potter, W; Cotter, G (2013)
In this paper we develop the jet model of Potter and Cotter to include a magnetically dominated accelerating parabolic base transitioning to a slowly decelerating conical jet with a geometry set by recent radio observations of M87. We conserve relativistic energy-momentum and particle number along the jet and calculate the observed synchrotron emission from the jet by calculating the integrated line-of-sight synchrotron opacity through the jet in the rest frame of each section of plasma. We calculate the inverse-Compton emission from synchrotron, cosmic microwave background (CMB), accretion disc, starlight, broad-line region (BLR), dusty torus and narrow-line region photons by transforming into the rest frame of the plasma along the jet. We fit our model to simultaneous multi-wavelength observations of the Compton-dominant FSRQ type blazar PKS 0227-369, with a jet geometry set by M87 and an accelerating bulk Lorentz factor consistent with simulations and theory. We investigate models in which the jet comes into equipartition at different distances along the jet and equipartition is maintained via the conversion of jet bulk kinetic energy into particle acceleration. We find that the jet must still be magnetically dominated within the BLR and cannot be in equipartition due to the severe radiative energy losses. The model fits the observations, including radio data, very well if the jet comes into equipartition outside the BLR within the dusty torus (1.5 pc) or at further distances (34 pc). The fits require a high-power jet with a large bulk Lorentz factor observed close to the line of sight, consistent with our expectations for a Compton-dominant blazar. We find that our fit in which the jet comes into equipartition furthest along the jet, which has a jet with the geometry of M87 scaled linearly with black hole mass, has an inferred black hole mass close to previous estimates. This implies that the jet of PKS 0227 might be well described by the same jet geometry as M87. © 2012 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.